Improving the protecting mechanisms of general property in the Russian Federation - Abramov, Vyacheslav Viktorovich; Abramov, Yury Viktorovich; Larisa Mikhailovna Zeynalova, Nikita Sergeevich Grudinin; Evgeniy Nikolaevich Lotorev, Yuriy Viktorovich Zemskov, Elena Viktorovna Kochetkova (Opción, 2019)
The aim of the study is to improve the protecting mechanisms of general property in the Russian Federation.The research is based on the dialectical method of cognition political, legal and socio-economic processes. As a result, information as an object of private property needs analysis and understanding of its essence, as well as determining the procedure for its consolidation, implementation and protection at the legislative level. In conclusion, development of the institution of private property and constitutional and legal mechanisms will help to strengthen the forms of private property, and change the social and economic situation in the state.